Is spacing really the “friend of induction”? - Verkoeijen, Peter; Bouwmeester, Samantha (Frontiers in Psychology, 2014)
Inductive learning takes place when people learn a new concept or category by observing a variety of exemplars. Kornell and Bjork (2008) asked participants to learn new painting styles either by presenting different paintings of the same artist consecutively (massed presentation) or by mixing paintings of different artists (spaced presentation). In their second experiment, Kornell and Bjork showed with a final style recognition test, that spacing resulted in better inductive learning than massing. Also, by using this style recognition test, they ruled out the possibility that spacing merely resulted in a better memory for the labels of the newly learned painting styles. The findings from Kornell and Bjork’s second experiment are important because they show that the benefit of spaced learning generalizes to complex learning tasks and outcomes, and that it is not confined to rote memory learning. However, the findings from Kornell and Bjork’s second experiment have never been replicated. In the present study we performed an exact and high-powered replication of Kornell and Bjork’s second experiment with a Web-based sample. Such a replication contributes to establish the reliability of the original finding and hence to more conclusive evidence of the spacing effect in inductive learning. The findings from the present replication attempt revealed a medium-sized advantage of spacing over massing in inductive learning, which was comparable to the original effect in the experiment by Kornell and Bjork. Also, the 95% confidence intervals of the effect sizes from both experiments overlapped considerably. Hence, the findings from the present replication experiment and the original experiment clearly reinforce each other.